2021
DOI: 10.1016/j.jbc.2021.100973
|View full text |Cite
|
Sign up to set email alerts
|

The detection and functions of RNA modification m6A based on m6A writers and erasers

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 166 publications
(381 reference statements)
0
32
0
Order By: Relevance
“…METTL3 was one of the key m 6 A methyltransferase which contained METTL3, WTAP, METTL14, and KIAA1429 ( Roundtree et al, 2017 ). M 6 A methyltransferase was involved in the post-transcriptional methylation of adenosine residues in the mRNA of eukaryotic cells to form N6-methyladenosine ( Zhang et al, 2021 ). In addition, studies have shown that METTL3 can directly act on the translation initiation machinery and promote m 6 A modification of mRNA, regardless of the activity of methyltransferase and m 6 A reader.…”
Section: Discussionmentioning
confidence: 99%
“…METTL3 was one of the key m 6 A methyltransferase which contained METTL3, WTAP, METTL14, and KIAA1429 ( Roundtree et al, 2017 ). M 6 A methyltransferase was involved in the post-transcriptional methylation of adenosine residues in the mRNA of eukaryotic cells to form N6-methyladenosine ( Zhang et al, 2021 ). In addition, studies have shown that METTL3 can directly act on the translation initiation machinery and promote m 6 A modification of mRNA, regardless of the activity of methyltransferase and m 6 A reader.…”
Section: Discussionmentioning
confidence: 99%
“…N 6 -methyladenosine (m 6 A) modification, the most frequent chemical modification in eukaryotic RNA, is involved in many biological processes including cancer progression [ 36 , 37 ]. Emerging studies highlighte that m6A modulates gene expression, thereby regulating tumor development aspects from cancer cell growth, metastasis, self-renewal of cancer stem cells, and apoptosis [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, RNA m6A methylation is catalyzed by a polyprotein complex composed of METTL3, METTL14, Wilms’ tumor 1-associating protein (WTAP), the human homolog of Drosophila Virilizer (KIAA1429) [ 56 ], and several cofactors not yet identified [ 57 , 58 ]. Their functions are summarized in Supplementary Table S1 .…”
Section: M6a Methylation Is One Of the Defense Mechanisms Against Pla...mentioning
confidence: 99%